(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
Highly transparent and well faceted large size epsomite single crystals have been grown in pure form and doped with KCl from aqueous solutions by slow cooling and isothermal evaporation method. The optical quality of the epsomite improves on doping by KCl. Mass growth rates were found to increase with doping of lower concentrations of KCl and then decreases with the higher concentration of KCl. KCl doped epsomite crystal reveals that structures are slightly distorted due to adsorption of Cl- ion into the crystal lattice. DC conductivity along the growth axis for all of the grown crystals increases with temperature in the range of 25 to 70ºC and also increases with the KCl concentration. Dielectric constant is found to be almost independent of frequency up to range of 106Hz. The dielectric studies show the suitability of these grown crystals for optoelectronic applications. DOI: 10.3329/jbas.v33i1.2949 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 47-54, 2009